Hepatoprotective effects of BPC-157 - paracetamol overdose - Sara Burić; Hrvoje Vraneš; Vlasta Vuković (Liječnički vjesnik, 2023)
Paracetamol, also known as acetaminophen, is a widely used medication to treat pain and fever. As it’s one of the over-the-counter medications, it’s easily accessible to everyone. Its mechanism of action is the inhibition of prostaglandin synthesis in the CNS to reduce hyperalgesia. It also influences the thermoregulatory center in the hypothalamus and lowers fever. 90-95% of paracetamol is metabolized in the liver where it’s conjugated with glucuronic acid and sulfates into inactive metabolites, and the rest via cytochrome-p450. Its main side effect is hepatotoxicity and acute liver injury. Here we investigate the hepatoprotective effects of BPC-157 while administering a toxic dose of paracetamol intraperitoneally in rats.